2013
DOI: 10.1118/1.4818825
|View full text |Cite
|
Sign up to set email alerts
|

Total target volume is a better predictor of whole brain dose from gamma stereotactic radiosurgery than the number, shape, or location of the lesions

Abstract: Purpose: To assess the hypothesis that the volume of whole brain that receives a certain dose level is primarily dependent on the treated volume rather than on the number, shape, or location of the lesions. This would help a physician validate the suitability of GammaKnife R based stereotactic radiosurgery (GKSR) prior to treatment. Methods: Simulation studies were performed to establish the hypothesis for both oblong and spherical shaped lesions of various numbers and sizes. Forty patients who underwent GKSR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…As shown by previous publications, the volume of tissue receiving specific isodose is proportional to the total target volume raised to an exponent [15, 17]. The primary framework is thus to define irradiated volume for a series of HF-RT patients as [15, 17]:where V primary (P) is volume of the external contour (EXT, entire volume inside the patient surface, including skull, skin, etc.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by previous publications, the volume of tissue receiving specific isodose is proportional to the total target volume raised to an exponent [15, 17]. The primary framework is thus to define irradiated volume for a series of HF-RT patients as [15, 17]:where V primary (P) is volume of the external contour (EXT, entire volume inside the patient surface, including skull, skin, etc.)…”
Section: Methodsmentioning
confidence: 99%
“…The primary framework is thus to define irradiated volume for a series of HF-RT patients as [15, 17]:where V primary (P) is volume of the external contour (EXT, entire volume inside the patient surface, including skull, skin, etc.) or Brain-Minus-PTV (BMP, the brain contour minus all target volumes) receiving dose P (percentage of prescription), PTV is the total target volume, and a(P) and b(P) are empirically determined fit-parameters for single, regularly-shaped targets.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that a decrease of 1-2 Gy in the prescription dose was recommended when 5 or more lesions were treated in order to reduce the risk of radiation toxicity. Conversely, Narayanasamy et al [28] assessed the effect of the number, shape, location of lesions and the total target volume on V12 Gy and found that only the total tumor volume was a significant factor for the prediction of radiation-related toxicity. Also, Xue et al [24] reported that the mean normal brain dose was correlated with the total target volume not the number of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested that the number of lesions is a significant predictive factor for radiation toxicity [26,27,29], others have advocated that the total target volume is important for predicting radiation-related brain injury [24,28]. Takahashi et al [26] suggested that the dose to the normal brain tissue increased with increasing numbers of targets in patients with multiple brain metastases treated with linac-based SRS; therefore, they recommended not treating more than 7 metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation